Experiential Avoidance, Dyadic Interaction and Relationship Quality in the Lives of Veterans and Their Partners. (April 2018) - Zamir, Osnat; Gewirtz, Abigail H.; Labella, Madelyn; DeGarmo, David S.; Snyder, James
This study assessed the mediating pathways of observed couple communication on the dyadic associations between experiential avoidance (EA) and relationship quality. A sample of 228 military couples following combat deployment participated in a conflict discussion and completed self-report measures to assess EA and relationship quality. Results of an actor–partner interdependence model using structural equation modeling indicated that for both dyad members greater EA was associated with their own lower relationship quality. Higher EA in men was associated with more observed negative communication, as well as lower relationship quality in their female partners. Positive couple communication was associated with higher relationship quality in men and in women. Overall, EA demonstrated associations with relationship quality above and beyond couple communication skills. This study points to the importance of EA for the marital system and suggests that interventions targeting EA and positive couple communication skills may strengthen military marital relationships following deployment to war.